Dhcr7 Regulates Palatal Shelf Fusion through Regulation of Shh and Bmp2 Expression. (15th March 2016) - Xiao, Wen-lin; Zhang, Dai-zun; Xu, Hong; Zhuang, Cui-zhu
Abstract : The aim of this study was to investigate the effect of the 7-dehydrocholesterol reductase ( Dhcr7 ) gene and identify signaling pathways involved in regulation of embryonic palatogenesis. The expression of Dhcr7 and its protein product were examined during murine normal embryonic palatogenesis via a reverse transcription polymerase chain reaction (RT-PCR) and Western blot (WB). RNA interference (RNAi) technology was used to inhibit Dhcr7 expression in a palatal shelf culture in vitro . The effects of Dhcr7 on palatogenesis and palatal fusion were examined by scanning electron microscopy (SEM). The expression changes of Dhcr7, Sonic Hedgehog (Shh), and bone morphogenetic protein-2 (Bmp2) were measured by RT-PCR and WB after Dhcr7 gene silencing and the addition of exogenous cholesterol. The results showed that the palatal shelf failed to complete normal development and fusion when Dhcr7 expression was inhibited. The inhibitory effect study of RNAi on the development of the palatal shelf supported that cholesterol supplementation did not alter the silencing of Dhcr7. Shh and Bmp2 expressions were reduced after Dhcr7 gene silencing, and administration of exogenous cholesterol did not affect Dhcr7 expression; however Shh and Bmp2 expressions increased. We conclude that Dhcr7 plays a role in growth of the palatal shelf and can regulate palatogenesis through alterations in the levels of Shh and Bmp2.